2022
DOI: 10.1007/s11469-022-00929-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Assessment and Gender Invariance of the Polish Version of the Gaming Disorder Test

Abstract: In 2019, Gaming Disorder (GD) was officially recognised by the World Health Organization (WHO) as an official mental health disorder. Currently, the Gaming Disorder Test (GDT) is one of the most widely utilised psychometric tools to assess GD symptoms according to the WHO framework. In this context, the present study aimed to develop the Polish version of the GDT so that this tool can be used within the Polish cultural context. Additionally, the research aimed to ascertain the psychometric properties and appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 90 publications
3
12
0
Order By: Relevance
“…To the best of the present authors’ knowledge, the present study is the first to translate and evaluate the psychometric properties of the Malay versions of the GDT and GADIS-YA among university students in Malaysia. Consistent with previous findings, the present study supported that the GDT has a single-factor structure (Cakiroglu & Alnak, 2021; Cudo et al, 2022b; Maldonado-Murciano et al, 2021; Montag et al, 2019; Pontes et al, 2021; Wang & Cheng, 2020) and the GADIS-YA has a two-factor structure (Mazaherizadeh et al, 2022; Nazari et al, 2022; Paschke et al, 2020). Furthermore, both the GDT and GADIS-YA demonstrated concurrent validity by significantly correlating with the IGDS9-SF, BSMAS, time spent on social media, and time spent on gaming.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To the best of the present authors’ knowledge, the present study is the first to translate and evaluate the psychometric properties of the Malay versions of the GDT and GADIS-YA among university students in Malaysia. Consistent with previous findings, the present study supported that the GDT has a single-factor structure (Cakiroglu & Alnak, 2021; Cudo et al, 2022b; Maldonado-Murciano et al, 2021; Montag et al, 2019; Pontes et al, 2021; Wang & Cheng, 2020) and the GADIS-YA has a two-factor structure (Mazaherizadeh et al, 2022; Nazari et al, 2022; Paschke et al, 2020). Furthermore, both the GDT and GADIS-YA demonstrated concurrent validity by significantly correlating with the IGDS9-SF, BSMAS, time spent on social media, and time spent on gaming.…”
Section: Discussionsupporting
confidence: 92%
“…The psychometric properties of the Malay version of the GDT demonstrated satisfactory level of internal consistency reliability in the present study, which was comparable to previous findings (Chiorri et al, 2023; Cudo et al, 2022b; Islam et al, 2022; Maldonado-Murciano et al, 2021). In concurrence with the existing literature (Islam et al, 2022; Wang & Cheng, 2020), the GDT score was found to be significantly correlated with the IGDS9-SF, BSMAS, time spent on social media, and time spent on gaming, supporting concurrent validity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, reported that female gamers used smartphones more often and desktop computers and stationary consoles less often as gaming platforms than male gamers. Also, it is essential to point out that female gamers usually present lower gaming disorder symptoms than male gamers (Cudo, Montag, et al, 2022;Su et al, 2020).…”
Section: Importance Of Gender Measurement Invariance For Risky Loot B...mentioning
confidence: 99%